Proton probing of laser-driven EM pulses travelling in helical coils. (13th February 2017) - Ahmed, H.; Kar, S.; Giesecke, A.L.; Doria, D.; Nersisyan, G.; Willi, O.; Lewis, C.L.S.; Borghesi, M.
Abstract : The ultrafast charge dynamics following the interaction of an ultra-intense laser pulse with a foil target leads to the launch of an ultra-short, intense electromagnetic (EM) pulse along a wire connected to the target. Due to the strong electric field (of the order of GV m^-1 ) associated to such laser-driven EM pulses, these can be exploited in a travelling-wave helical geometry for controlling and optimizing the parameters of laser accelerated proton beams. The propagation of the EM pulse along a helical path was studied by employing a proton probing technique. The pulse-carrying coil was probed along two orthogonal directions, transverse and parallel to the coil axis. The temporal profile of the pulse obtained from the transverse probing of the coil is in agreement with the previous measurements obtained in a planar geometry. The data obtained from the longitudinal probing of the coil shows a clear evidence of an energy dependent reduction of the proton beam divergence, which underpins the mechanism behind selective guiding of laser-driven ions by the helical coil targets.